PENGARUH BAHAN BAKU DAN MANAJEAMEN RANTAI PASOKAN TERHADAP PROSES PRODUKSI PT. NIRO CERAMIC NASIONAL INDONESIA - Muhammad Yasman Suudi; Edy Sanusi Silitonga (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2021)
The aim of this study was to find out the raw of materials and supply chain management impact to company’s production progress. Population from this research are employee production division of PT. Niro Ceramic Nasional Indonesia as more as 250 persons and sample used are 130 respondents. Research method used is quantitative method, analysis technique multiple regression and simple regression. The results of this study indicate that simultaneously the raw of materials and supply chain management 45,9 % from the progress of production. 31,7 %. and from the Raw of materials to production process 16,0 % from the supply chain management to production process.